Performance improvement of non-sintering permeable brick with the addition of fibers at a low content. (November 2021) - Han, Hong; Ju, Chenggong; Yan, Wenzhe; Yang, Mao; Wan, Qianqian; Li, Qiqi; Wu, Yan
Abstract: At present, a large amount of land is occupied and the environment is polluted due to the production and accumulation of massive dredged sediment. At the same time, the construction of "sponge cities" is imminent, wherein there is a great demand for permeable brick. Here, a kind of eco-friendly non-sintering dredged sediment permeable brick (DSPB) was developed from wrap-shell lightweight aggregates (WSLAs). To improve the performance of DSPB, polypropylene fibers (PPFs), carbon fibers (CFs) and glass fibers (GFs) of low content were added to it separately, and the optimum type, content, and mixing ratio for fibers were determined by evaluating the compressive strength, water permeability coefficient and strength loss rate of fibers-laden DSPB. It was found that GFs significantly improve the performance of DSPB. When the GFs content was 2.0 kg/m 3 and the mixing ratio was 3:7 (GFs in WSLAs shell: GFs in cementitious material), the compressive strength, water permeability coefficient and strength loss rate of GFs-laden DSPB were 16.4 MPa, 0.202 mm/s and 9.76%, respectively. The above test results met the requirement of Chinese National Standards (CJ/T 400–2012). Compared with the unreinforced ones, the permeability coefficient of the GFs-laden DSPB remained unchanged with compressive strength 30.2% higher, and the strength loss rate was reduced by 23.1%. The point-to-point connection structure in GFs-laden DSPB was observed by scanning electron microscope (SEM) and polarizing microscope (PM). GFs play a crack resistance effect at point-to-point connection zone and in WSLAs shell, which is beneficial to improve the overall strength and frost resistance of DSPB. The addition of GFs at a low content has significantly improved the performance of DSPB in this study, and this method can be applied in pavement and further shed light to the new way of production of economical, non-sintering and high-strength building materials. Graphical abstract: Image 1 Highlights: The performance of a kind of dredged sediment permeable brick (DSPB) is improved. Glass fibers (GFs) notably reinforce the DSPB compared with the other two fibers. GFs at point-to-point connection in DSPB show a good anti-crack effect. GFs impart superior ability to resist freezing and thawing to DSPB. Proper GFs content and distribution is critical to the strength of DSPB.